The Linguacultural Speech Patterns of the Marvel Universe Characters (MCU) and Translation Issues - Islam Аybarsha; Kozhbayeva, Gulbakyt; Karibayeva, Buadat; Khamrayeva, Shakhidam; Kurmanbayeva, Dametken; Sopieva, Bayan (Forum for Linguistic Studies, 2025)
This study investigates the linguacultural speech patterns of characters in the Marvel Cinematic Universe (MCU) and the challenges associated with their translation. Through a detailed linguacultural analysis of selected MCU films, it examines how character speech serves as a marker of cultural identity, social status, and professional background. Particular attention is given to how these elements manifest through lexical choices, idiomatic expressions, slang, sociolects, and intertextual references. Speech is categorized according to cultural, social, and professional markers, with emphasis on the inclusion of non-American cultural expressions, generational language features (such as youth slang), and context specific linguistic variations that contribute to character development and narrative authencity. The study examines the translation strategies, applied in official dubbed or subtitled versions, focusing on domestication and foreignization as key approaches to cultural adaptation. Findings suggest that although humor, sarcasm, and general tone are often preserved, many character-specific cultural distinctions and identity markers tend to be simplified or lost in translation. This loss can influence how non-English-speaking audiences perceive individual characters, particularly in terms of their distinctcultural or social identity. By addressing these issues, the research contributes to discussions in audiovisual translation theory, intercultural communication, and the representation of cultural identity in globalized media storytelling.